2019
DOI: 10.1111/gbb.12593
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CELF6 RNA binding protein impairs cocaine conditioned place preference and contextual fear conditioning

Abstract: In addition to gene expression differences in distinct cell types, there is substantial post‐transcriptional regulation driven in part by RNA binding proteins (RBPs). Loss‐of‐function RBP mutations have been associated with neurodevelopmental disorders, such as Fragile‐X syndrome and syndromic autism. Work performed in animal models to elucidate the influence of neurodevelopmental disorder‐associated RBPs on distinct behaviors has showed a connection between normal post‐transcriptional regulation and condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Marble burying is a natural murine behavior and has been used to indicate repetitive digging as well as anxiety-related behaviors. Protocol was adapted from previously published methods (Lazic, 2015;Maloney et al, 2019a). In brief, 8-week old mice were placed in a transparent enclosure (28.5 cm x 17.5 cm x 12 cm) with clean aspen bedding and 20 dark blue marbles evenly spaced in a 4 3 5 grid on top of the bedding.…”
Section: Marble Buryingmentioning
confidence: 99%
See 1 more Smart Citation
“…Marble burying is a natural murine behavior and has been used to indicate repetitive digging as well as anxiety-related behaviors. Protocol was adapted from previously published methods (Lazic, 2015;Maloney et al, 2019a). In brief, 8-week old mice were placed in a transparent enclosure (28.5 cm x 17.5 cm x 12 cm) with clean aspen bedding and 20 dark blue marbles evenly spaced in a 4 3 5 grid on top of the bedding.…”
Section: Marble Buryingmentioning
confidence: 99%
“…Fear conditioning was done as previously described (Maloney et al, 2019a(Maloney et al, , 2019b. Mice were habituated to an acrylic chamber (26 cm x 18 cm x 18 cm) containing a metal grid floor and an odorant and was illuminated by LED light which remained on for the Cell Reports 33, 108416, November 24, 2020 e6 Article ll OPEN ACCESS duration of the trial.…”
Section: Conditioned Fearmentioning
confidence: 99%
“…CELF6 showed expression in the hypothalamus and in several monoaminergic cell populations commonly targeted in psychiatry ( Maloney et al, 2016 ). Likely as a consequence of its role in those cells, it is also associated with conditioned behaviors: Celf6- knockout (KO) mouse pups show altered ultrasonic vocalization, while adults exhibit deficits in fear conditioning and loss of conditioned place preference to cocaine ( Dougherty et al, 2013 ; Maloney et al, 2019 ). Although capable of regulating splicing in vitro ( Ladd et al, 2004 ), CELF6 has recently been shown to interact with the 3′ untranslated region (UTR) as well, allowing it to stabilize p21 mRNA in colorectal cancer cells ( Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Marble burying is a natural murine behavior and has been used to indicate repetitive digging as well as anxiety-related behaviors. Protocol was adapted from previously published methods (Lazic, 2015;Maloney et al, 2019a). In brief, 8-week old mice were placed in a transparent enclosure (28.5 cm x 17.5 cm x 12 cm) with clean aspen bedding and 20 dark blue marbles evenly spaced in a 4 x 5 grid on top of the bedding.…”
Section: Marble Buryingmentioning
confidence: 99%
“…Fear conditioning was done as previously described (Maloney et al, 2019a(Maloney et al, , 2019b. Mice were habituated to an acrylic chamber (26 cm x 18 cm x 18 cm) containing a metal grid floor and an odorant and was illuminated by LED light which remained on for the duration of the trial.…”
Section: Conditioned Fearmentioning
confidence: 99%